Treatment of Candida glabrata Infection in Immunosuppressed Mice by Using a Combination of Liposomal Amphotericin B with Caspofungin or Micafungin - Jon Olson; Jill Adler‐Moore; Peter J. Smith; Richard T. Proffitt (2005)
ABSTRACT While Candida albicans remains the most common Candida isolate, Candida glabrata accounts for approximately 15 to 20% of all Candida infections in the United States. In this study we used immunosuppressed mice infected with C. glabrata to investigate the efficacy of liposomal amphotericin B alone or in combination with the echinocandin caspofungin or micafungin. For monotherapy, mice were given six daily doses of liposomal amphotericin B (3 to 20 mg/kg of body weight), caspofungin (1 to 5 mg/kg), or micafungin (2.5 to 10 mg/kg). With concomitant therapy, mice received liposomal amphotericin B (7.5 mg/kg) in addition to caspofungin (2.5 mg/kg) or micafungin (2.5 mg/kg) for 6 days. For sequential therapy, liposomal amphotericin B was administered on days 1 to 3 and caspofungin or micafungin was given on days 4 to 6; conversely, caspofungin or micafungin was administered on days 1 to 3 and liposomal amphotericin B was given on days 4 to 6. Efficacy was based on the number of CFU per gram of kidney 21 days postchallenge. Monotherapy with liposomal amphotericin B (7.5 to 20 mg/kg) was significantly more effective than no drug treatment (control group) ( P < 0.05) and demonstrated a dose-dependent response, with 20 mg/kg lowering the CFU/g from 6.3 to 4.2 (significantly different from the value for the control group [ P < 0.001]). Monotherapy with all echinocandin doses lowered the CFU/g from 6.0 to 6.4 to 2.7 to 3.3 (significantly different from the value for the control group [ P < 0.001]) with no dose-dependent response. Complete clearance of infection could be achieved only when liposomal amphotericin B was given either concomitantly with caspofungin or micafungin or if liposomal amphotericin B was given sequentially with caspofungin. In conclusion, the combination of liposomal amphotericin B with an echinocandin markedly improved the therapeutic outcome in murine C. glabrata systemic infection.